If the function RX) = (2x-3) is transformed to g(x) = (-2x-3), which type of transformation occurred?
A
B.
c.
horizontal shift
vertical reflection
vertical shift
D. horizontal reflection
Reset
Next
202 Edimentum All right

Respuesta :

Answer: Vertical reflection.

Step-by-step explanation:

 The correct exercise is: "If the parent function[tex]f(x) = (2x - 3)^3[/tex] is transformed to [tex]g(x) = (-2x + 3)^3[/tex] , which type of transformation occurs?

There are several transformations for a function f(x). Two of them are shown below:

1. If [tex]-f(x)[/tex], then the function is reflected across the x-axis (Vertical reflection).

2. If [tex]f(-x)[/tex], then the function is reflected across the y-axis (Horizontal reflection).

In this case, the exercise provides you the following function f(x):

[tex]f(x) = (2x - 3)^3[/tex]

And you know that the function g(x) is obtained by transforming the function f(x).

The function g(x) give is:

 [tex]g(x) = (-2x + 3)^3[/tex]

 Which can written as:

[tex]g(x) = -(2x - 3)^3[/tex]

 Therefore, you can identify (based on the transformations shown at the beginning of the explanation), that:

[tex]g(x)= -f(x)[/tex]

Therefore, the function   [tex]g(x) = (-2x + 3)^3[/tex]  is obtained by reflecting the function  [tex]f(x) = (2x - 3)^3[/tex]  across the x-axis.